MIR93 (microRNA -93) regulates tumorigenicity and therapy response of glioblastoma by targeting autophagy. Issue 6 (3rd June 2019) - Huang, Tianzhi; Wan, Xuechao; Alvarez, Angel A.; James, C. David; Song, Xiao; Yang, Yongyong; Sastry, Namratha; Nakano, Ichiro; Sulman, Erik P.; Hu, Bo; Cheng, Shi-Yuan
ABSTRACT: Macroautophagy/autophagy is a natural intracellular process that maintains cellular homeostasis and protects cells from death under stress conditions. Autophagy sustains tumor survival and growth when induced by common cancer treatments, including IR and cytotoxic chemotherapy, thereby contributing to therapeutic resistance of tumors. In this study, we report that the expression of MIR93, noted in two clinically relevant tumor subtypes of GBM, influenced GSC phenotype as well as tumor response to therapy through its effects on autophagy. Our mechanistic studies revealed that MIR93 regulated autophagic activities in GSCs through simultaneous inhibition of multiple autophagy regulators, including BECN1/Beclin 1, ATG5, ATG4B, and SQSTM1/p62. Moreover, two first-line treatments for GBM, IR and temozolomide (TMZ), as well as rapamycin (Rap), the prototypic MTOR inhibitor, decreased MIR93 expression that, in turn, stimulated autophagic processes in GSCs. Inhibition of autophagy by ectopic MIR93 expression, or via autophagy inhibitors NSC (an ATG4B inhibitor) and CQ, enhanced the activity of IR and TMZ against GSCs. Collectively, our findings reveal a key role for MIR93 in the regulation of autophagy and suggest a combination treatment strategy involving the inhibition of autophagy while administering cytotoxic therapy. Abbreviations: ACTB: actin beta; ATG4B: autophagy related 4B cysteine peptidase; ATG5: autophagy related 5; BECN1: beclin 1; CL: classical; CQ: chloroquine diphosphate; CSCs: cancer stem cells; GBM: glioblastoma; GSCs: glioma stem-like cells; HEK: human embryonic kidney; IB: immunoblotting; IF: immunofluorescent staining; IR: irradiation; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MES: mesenchymal; MIR93: microRNA 93; MIRC : a control miRNA; miRNA/miR: microRNA; MTOR: mechanistic target of rapamycin kinase; NSC: NSC185085; PN: proneural; qRT-PCR: quantitative reverse transcription-polymerase chain reaction; Rap: rapamycin; SQSTM1/p62: sequestosome 1; TCGA: the cancer genome atlas; TMZ: temozolomide; WT: wild type; ZIP93 : lentiviral miRZIP targeting MIR93; ZIPC : lentiviral miRZip targeting control miRNA